The PCE in the magnifying glass of the Political Social Brigade. The communists in the police bulletins (1938-1975) - Alcántara Pérez, Pablo (Hispania Nova, 2021)
The communists, and specifically the PCE, have always been one of the main objectives of the Francoist public order forces. Both for becoming, over the decades, the main force of opposition to the regime through the labor, student movement and later in other social sectors such as intellectuals, culture or the liberal professions, and for the intrinsic anti-communism of the regime. For this reason, the police, and specifically the Political Social Brigade, pay special attention to it when carrying out their analysis of the country’s internal situation. At first, through the well-known Anti-Marxist Bulletins, carried out by Eduardo Comín Colomer, police and propagandist writer, and which lasted from 1938 to 1945, and which have a more ideological than practical content. Starting in 1946, the Social Investigation Bulletins began to be published, which contain more precise information about the arrests, the people they arrest, the propaganda they seized, etc. The idea of this article would be to make a comparative analysis of how the vision of communists throughout the dictatorship by the BPS is changing, according to their interests, police practices, through these reports, one of the main police sources.